1997
DOI: 10.1046/j.1365-2826.1997.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Behavioural Responses to Noise Stress:Comparison of Virgin and Lactating Female Ratsduring Non‐Disrupted Maternal Activity

Abstract: The behavioural and endocrine responses to a 10 min white noise stress have been characterized in female virgin and undisturbed lactating Sprague-Dawley rats. Animals were continuously video-taped and frequent blood samples were collected using an automated sampling system. Noise stress caused hypothalamo-pituitary-adrenal (HPA) activation, as indicated by a rapid increase in plasma corticosterone and ACTH in the virgins: corticosterone concentrations peaked 20 min after initiation of the stress before declini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(167 citation statements)
references
References 5 publications
13
149
3
2
Order By: Relevance
“…In accordance with the present results suggesting that direct adrenal effects of PRL may be important for steroidogenesis in the response to stress, there are observations from animal studies in which glucocorticoid levels can remain elevated during stress, despite de- clining CRH and/or ACTH concentrations [20,21,[40][41][42]. Previous studies have demonstrated that exercise stress induced an increase in circulating PRL in humans [43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the present results suggesting that direct adrenal effects of PRL may be important for steroidogenesis in the response to stress, there are observations from animal studies in which glucocorticoid levels can remain elevated during stress, despite de- clining CRH and/or ACTH concentrations [20,21,[40][41][42]. Previous studies have demonstrated that exercise stress induced an increase in circulating PRL in humans [43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies on the inhibitory influence of OT on stress-responsive neurohormonal systems focused on the endogenous stimulation of OT during lactation in rodents. The suckling stimulus by the newborn was found to increase OT release and decrease basal plasma levels of ACTH and cortisol [26,27,121,148,149,160].…”
Section: Social Stress and Anxietymentioning
confidence: 98%
“…Lactation also blunts HPA axis reactivity to several stressors in rats including white noise [78], elevated plusmaze [79], forced swimming [79,80], acute cold exposure [81], and lipopolysaccharide injection [82]. Furthermore, corticosteroid response to ether stress is inversely related to litter size [83].…”
Section: Possible Mechanism Underlying Social Buffering Of the Hpa Axismentioning
confidence: 99%